PENTINGNYA STIMULASI MOTORIK HALUS UNTUK MENINGKATKAN KEMAMPUAN MENULIS PADA ANAK TK B - Maria Evaristine Dian Pambudi; Miranda Claudya Anugrahni; Andri Anugrahana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the importance of fine motor stimulation to improve children's writing skills in Kindergarten (TK) B. The research method used is descriptive qualitative research, with data collection techniques in the form of observation, interviews and documentation. The research results show that there are 21.74% of children who still have difficulty holding writing instruments and have not fully mastered basic writing skills such as recognizing and following letter patterns or shapes. The research results show that fine motor stimulation, especially through the tracing method, has an important role in improving writing skills in children aged 5-6 years or at kindergarten age level. The tracing method helps children train eye and hand coordination and control hand movements, thus training the child's finger muscles and getting children used to being able to recognize patterns or letter shapes. Apart from that, this method can also increase children's concentration, patience, perseverance and creativity. So, with the tracing method, children can develop fine motor skills and improve children's writing abilities at the kindergarten age level.